Alien grass infestation in renosterveld fragments: effect on threatened life history types and potential controls - Stanway, Rosanne (Department of Biological Sciences, 2026)
Alien grasses are thought to pose a significant threat to the growth and survival of Indigenous species. Within the Cape Floristics Region, there Is concern surrounding the establishment of alien grasses in renosterveld fragments.